2017
DOI: 10.1590/2359-3997000000236
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity index and triglyceride/high-density lipoprotein cholesterol ratio in hypogonadism

Abstract: Background: Cardiometabolic risk is high in patients with hypogonadism. Visceral adiposity index (VAI) and triglyceride/high-density lipoprotein cholesterol (TG/HDL-C) ratio are the practical markers of atherosclerosis and insulin resistance and independent predictors of cardiaovascular risk. To date, no study has evaluated VAI levels and TG/HDL-C ratio in hypogonadism. Subjects and methods: A total of 112 patients with congenital hypogonadotrophic hypogonadism (CHH) (mean age, 21.7 ± 2.06 years) and 124 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
1
8
0
2
Order By: Relevance
“…1214 Testosterone deficiency is associated with visceral fat dysfunction, subsequent chronic inflammation, insulin resistance and low sex hormone binding globulin (SHBG) levels. 15,16 Weight loss achieved pharmacologically with liraglutide 17 or with bariatric surgery improved testosterone and gonadotrophin levels, and were able to reverse the hypogonadotrophic hypogonadism caused by obesity. 1820…”
Section: Pathophysiology Of Male Obesity-related Secondary Hypogonadismmentioning
confidence: 99%
“…1214 Testosterone deficiency is associated with visceral fat dysfunction, subsequent chronic inflammation, insulin resistance and low sex hormone binding globulin (SHBG) levels. 15,16 Weight loss achieved pharmacologically with liraglutide 17 or with bariatric surgery improved testosterone and gonadotrophin levels, and were able to reverse the hypogonadotrophic hypogonadism caused by obesity. 1820…”
Section: Pathophysiology Of Male Obesity-related Secondary Hypogonadismmentioning
confidence: 99%
“…Essa medida está associada ao aumento do risco de DCV e consequente mortalidade. (BORRAYO et al, 2018;HAJIAN-TILAKI;HEIDARI;BAKHTIARI, 2020;HAYMANA et al, 2017) A relação TG / HDL tem forte associação positiva com HOMA-IR na população. Portanto, consiste em um método fácil e parâmetro econômico em contextos clínicos, atuando como um marcador substituto para RI, disfunção endotelial e inflamação.…”
Section: Resultados E/ou Discussão (Ou Análise E Discussão Dos Result...unclassified
“…Portanto, consiste em um método fácil e parâmetro econômico em contextos clínicos, atuando como um marcador substituto para RI, disfunção endotelial e inflamação. (CHUNG;KWON;LEE, 2020;DI BONITO et al, 2012;HAYMANA et al, 2017) A DT sérica tem sido associada à obesidade, DM2, SM e aterosclerose, além do aumento da mortalidade por todas as causas em homens. Indivíduos com essas comorbidades têm maior risco de morte prematura e outros efeitos adversos à saúde.…”
Section: Resultados E/ou Discussão (Ou Análise E Discussão Dos Result...unclassified
“…Hypertriglyceridemia was another factor significantly associated with primary hypogonadism in male SSc patients. Hypertriglyceridemia has been reported to be related to hypogonadism 35,36 and increased TG levels with low levels of high-density lipoprotein (HDL), which are features of males with hypogonadism. 36 Haymana et al 36 also reported that a high TG/HDL ratio was correlated with endothelial dysfunction and inflammation.…”
Section: Discussionmentioning
confidence: 99%